Revision of the genus Leptobatopsis Ashmead, 1900 (Hymenoptera, Ichneumonidae, Banchinae) from Japan, with some taxonomic notes of Asian species - Watanabe, Kyohei; Ito, Masato (Zootaxa, 2023)
The Japanese species of the genus Leptobatopsis Ashmead, 1900 are revised. A total of eight species are recorded from Japan, including a new species, Leptobatopsis yaima sp. nov., and three species, L. annularis Kasparyan, 2007, L. koreana Lee & Kang, 2015, and L. nigricapitis Chandra & Gupta, 1977, newly recorded from Japan. A Chinese species L. annularis Sheng & Sun, 2013 is a homonym of L. annularis Kasparyan, 2007. Both species are clearly different, and we therefore propose a new replacement name for the former, L. sinica (nom. nov.). Leptobatopsis daedeokensis Lee & Kang, 2015 is newly synonymised with L. annularis Kasparyan, 2007. The taxonomic position of L. nigra immaculata Momoi, 1971 is changed from a subspecies of L. nigra Cushman, 1933 to separate species, L. immaculata. The female of L. badia Momoi, 1970 is newly described. A key to the Japanese species of this genus is proposed.